Prevalence of subclinical mastitis and antibiotic resistant bacteria in three selected cattle farms in Serdang, Selangor and Kluang, Johor - Othman, Norlida; Bahaman, Abdul Rani (Veterinary Association Malaysia, 2005)
Sixty cows from three established cattle farms in Serdang and Kluang were randomly selected and examined for mastitis. A high (81.7%) prevalence of subclinical mastitis was seen amongst the animals examined as indicated by the California Mastitis Test (CMT). The prevalence of subclinical mastitis in the farms ranged from 75 to 95%. Thirteen bacterial genera were identified from the 126 isolates obtained. Staphylococcus aureus appeared to be the most predominant bacteria in the milk samples. This was followed by Micrococcus spp., Corynebacterium spp., Staphylococcus epidermidis and Streptococcus spp. These Gram-positive organisms made up almost 75% (95/126) of the isolates seen in the milk samples. Most of the organisms showed antibiotic resistance to tetracycline, chloramphenicol and sulphonamides. Fourteen (38.9%) of the Staphylococcus aureus isolates showed resistance to penicillin. The isolation of these bacterial species has given some insights into the distribution, pathogenicity and role of these organisms in bovine mastitis in Malaysia. The high prevalence of subclinical mastitis seen in all three farms warrants a more effective mastitis control measure.